Methods of Digital Technologies and Online Platforms in The Promotion and Sale of Wedding Dresses - Iryna Kotapska (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
The article examines existing methods of digital technologies and online platforms as tools for promoting and selling wedding dresses. The relevance of the study is determined by the rapid, nearly exponential, increase in the influence of information and communication technologies and Internet platforms on consumer behavior patterns and the formation of business strategies in the bridal wear industry. The aim of the work is to conduct an in-depth analysis and systematization of contemporary approaches to the application of digital tools and Internet resources in order to enhance the effectiveness of marketing promotion strategies and processes and the commercial realization of wedding attire. The research is based on a methodology that includes analysis of recent scholarly publications and empirical market research data. Within the framework of the study, a detailed examination is carried out of the most significant digital means, among which are social media and influencer marketing, specialized e-commerce platforms, as well as innovative solutions in the field of augmented (AR) and virtual (VR) reality. This article is intended for a wide range of specialists: researchers in the fields of digital marketing and e-commerce, professionals in the wedding industry, as well as entrepreneurs seeking to optimize business models and increase competitiveness in the market of exclusive bridal wear. As a result of the systematic analysis, fundamental conclusions are formulated regarding the necessity of applying a comprehensive, multichannel approach when establishing a presence in the digital space, and it is also confirmed that deep personalization of commercial offers and interactive engagement with the target audience—particularly prospective brides—are key factors for success under contemporary market conditions. [References maintained in square brackets].